2021
DOI: 10.1111/agec.12656
|View full text |Cite
|
Sign up to set email alerts
|

Price formation within Egypt's wheat tender market: Implications for Black Sea exporters

Abstract: Black Sea wheat exporters, led by Russia, dominate Egypt's wheat imports via a tender system. The tenders are managed by the GASC and their outcomes are communicated worldwide by financial news agencies. Building on a transaction‐specific dataset on GASC tenders (2011 ‐ 2019), results of our cointegration analysis find wheat export markets of Russia, France and the USA highly integrated with the GASC tender price. Estimates from the multivariate VECM indicate strong price interdependencies between the GASC ten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 39 publications
1
8
0
1
Order By: Relevance
“…Some scientists believe that over the last two decades, the Black Sea region developed to be a key global exporting region for corn and wheat [7]. We fully agree with Heigermoser et al, who note that many market participants grapple with insufficient knowledge of factors that drive Black Sea spot prices, while effective futures markets that could facilitate price discovery and risk management are still missing.…”
Section: Literature Reviewsupporting
confidence: 73%
“…Some scientists believe that over the last two decades, the Black Sea region developed to be a key global exporting region for corn and wheat [7]. We fully agree with Heigermoser et al, who note that many market participants grapple with insufficient knowledge of factors that drive Black Sea spot prices, while effective futures markets that could facilitate price discovery and risk management are still missing.…”
Section: Literature Reviewsupporting
confidence: 73%
“…For example, in 2020, Egypt imported 60% (5.8 million t) of its wheat from Russia, 26% (2.5 million t) from Ukraine, and 7% (0.6 million t) from France [26]. Heigermoser et al [18] found interdependencies between the GASC prices and the export prices in Russia and France, with a leading role from France (but not Russia) in the formation of the tender prices.…”
Section: The State Of Play On the World Wheat Marketmentioning
confidence: 99%
“…In contrast to Ghoshray [16], we add to the existing literature on global grain market integration by providing an upto-date analysis that includes wheat prices from the Black Sea region. Although Svanidze et al [17] and Heigermoser et al [18] included the Black Sea exporters in their analysis of the world wheat prices, both of the studies exclusively focused on the price relationships between the wheat importing and exporting countries. In particular, they found that the Black Sea markets have become increasingly important for the price formation of the domestic wheat markets in net-importing countries of the South Caucasus and Central Asia [17], as well as Egypt [18].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This paper contributes to the broader (and older) literature on spatial market integration analysis as well as to the more recent literature on the impact of the COVID‐19 pandemic and policy responses on the functioning of food systems and markets. By evaluating spatial market integration during normal times and during a pandemic, we contribute nuanced empirical evidence to the literature evaluating spatial food market (dis)integration in Africa (Abdulai, 2000; Abay et al., 2023; Asche et al., 2011; Badiane & Shively, 1998; De Matteis et al., 2021; Dillon & Barrett, 2016; Hastings et al., 2021; Heigermoser et al., 2021; Jones & Salazar, 2021). Despite substantial variations across food items and across time (before and during the pandemic), we show significant spatial market integration prior to the pandemic and that patterns of integration declined after its outbreak.…”
Section: Introductionmentioning
confidence: 99%